Icelandic as a shared language : a rendezvous for immigrants and locals - Annalou A. Perez 1980- (2020)
Immigration requires adaptability to change, including adjustments to a new country’s language and system of communication. This is particularly challenging in Iceland because many Icelanders attach symbolic value to the language and consider the language itself as ‘pure’ and potentially endangered by contact with other languages (Skaptadóttir & Innes, 2016; Trililani, 2015). This stance prevails in spite of language being considered a flexible system of communication that naturally changes over time (Langer & Nesse, 2012), and contrasts with the “Resolution on the status of the Icelandic language” (Icelandic Language Council, 2018), which encourages Icelanders to be considerate towards people of foreign origin and their less-than-perfect usage of the Icelandic language. Recent studies have shown that insufficient Icelandic language skills can lead to immigrants´ isolation within society as well as exclusion in the workplace (Burdikova et al., 2018; Christiansen & Kristjánsdóttir, 2016; Skaptadóttir & Innes, 2016). Research also indicates that many learners are dissatisfied with their Icelandic language instruction and subsequent language learning experiences (Renner, 2010; Sölvason & Meckl, 2019; Þórisdóttir et al., 1997). This study (1) provides understanding of how immigrants learn Icelandic and use it in their communities, and (2) identifies approaches that can effectively support social integration through language learning. Employing a qualitative research design, the experiences of ten adult Filipino immigrants living outside the capital area were collected through in-depth interviews, then analysed through an interpretative phenomenological process. Results indicate that immigrants who had discouraging experiences in their communities expressed anxiety, self-doubt, and insecurity, and tended to use a strategy of switching to English. Immigrants who had favourable language learning experiences were more motivated to speak Icelandic in daily life, enhancing their language adaptability. ...